2016
DOI: 10.1007/s10661-016-5581-z
|View full text |Cite
|
Sign up to set email alerts
|

Ozone levels in the Spanish Sierra de Guadarrama mountain range are above the thresholds for plant protection: analysis at 2262, 1850, and 995 m a.s.l.

Abstract: The Sierra de Guadarrama mountain range, located at 60 km from Madrid City (Spain), includes high valuable ecosystems following an altitude gradient, some of them protected under the Sierra de Guadarrama National Park. The characteristic Mediterranean climatic conditions and the precursors emitted from Madrid favor a high photochemical production of ozone (O) in the region. However, very little information is available about the patterns and levels of O and other air pollutants in the high elevation areas and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 71 publications
0
13
0
Order By: Relevance
“…Ozone treatments were: charcoal filtered air (FA) mirroring the natural preindustrial background levels, non-filtered air (NFA) reproducing ambient levels of the farm and non-filtered air supplemented with 20 and 40 nL L -1 of O3 (NFA+ and NFA++ respectively) over an 8-hour period (07:00 to 15:00 GTM). Maximum hourly values at NFA++ during the exposure period ranged between 90-110 nL L -1 to achieve the sporadically maximum levels observed on the 10-year study of the O3 levels at Sierra de Guadarrama Mountains (Elvira et al, 2016).…”
Section: Experimental Design and Ozone Treatmentsmentioning
confidence: 78%
See 2 more Smart Citations
“…Ozone treatments were: charcoal filtered air (FA) mirroring the natural preindustrial background levels, non-filtered air (NFA) reproducing ambient levels of the farm and non-filtered air supplemented with 20 and 40 nL L -1 of O3 (NFA+ and NFA++ respectively) over an 8-hour period (07:00 to 15:00 GTM). Maximum hourly values at NFA++ during the exposure period ranged between 90-110 nL L -1 to achieve the sporadically maximum levels observed on the 10-year study of the O3 levels at Sierra de Guadarrama Mountains (Elvira et al, 2016).…”
Section: Experimental Design and Ozone Treatmentsmentioning
confidence: 78%
“…Mediterranean mountains, which are hot spots for biodiversity (Myers et al, 2000) and frequently belong to protected areas like National Parks or Nature 2000 Network, are currently suffering extensively from elevated levels of tropospheric ozone (Saavedra et al, 2012;Adame and Sole, 2013;Elvira et al, 2016). In the Sierra de Guadarrama mountains, the O3 levels recorded during the 2005-2011 period indicated that concentrations of this pollutant exceed the thresholds for human health, and can be more than three-fold above the standard values for plant protection, according to the Air Quality Directive EU/50/2008 (Elvira et al, 2016). Thus, a tropospheric O3 increase should be considered as a stress factor for the health of these ecosystems and their constituent parts.…”
Section: Bdmentioning
confidence: 99%
See 1 more Smart Citation
“…This implies that GNP will undergo a drastic change in its environmental conditions and that in the foreseeable future this would suppose the appearance of remarkably different environmental conditions from those that were considered in its creation as national park. This could be a risk for the persistence of this reserve and the biodiversity that or how vegetation is affected by pollutants arriving from the city of Madrid (Elvira et al 2016). All these studies raise the alarm over the risks and negative impacts that may appear in this national park.…”
Section: Policy Implicationsmentioning
confidence: 96%
“…It can be considered a global hazard. Indeed, there are mountains particularly exposed to air masses that bring high ozone concentrations from source areas (Elvira et al 2016). Ozone is harmful both to plants and humans.…”
Section: Atmospheric Contaminantsmentioning
confidence: 99%